Integration of morphological and molecular data reveals further unknown diversity of the Proterodiplostomidae in crocodilians. Issue 1 (21st March 2022) - Achatz, Tyler J.; Chermak, Taylor P.; Junker, Kerstin; Tkach, Vasyl V.
Abstract : The Proterodiplostomidae Dubois, 1936 is a family of digeneans within the superfamily Diplostomoidea Poirier, 1886. Members of the family are distributed mostly in the tropics and subtropics, primarily in crocodilians, although some species are known from other reptiles. Despite their broad geographic distribution, the knowledge of proterodiplostomid diversity remains limited, mostly because a number of potential host species and regions of the world have not been sufficiently explored for these parasites. In this study, we use morphological and molecular data to describe four new genera ( Afroproterodiplostomum gen. nov., Dungalabatrema gen. nov., Australiadiplostomum gen. nov. and Nattererodiplostomum gen. nov.) and five new species ( Afroproterodiplostomum ingwenyae sp. nov., Australiadiplostomum blairi sp. nov., Dungalabatrema kostadinovae sp. nov., Dungalabatrema snyderi sp. nov. and Pseudoneodiplostomum angustus sp. nov.) of proterodiplostomids from crocodilians in Australia, South Africa and South America. Nattererodiplostomum gen. nov. has been established upon re-evaluation of the status of Proterodiplostomum medusae (Dubois, 1936) from caimans in Brazil using combined morphological and molecular evidence. Only a few previous studies provided DNA sequence data of proterodiplostomids. We generated partial 28S rDNA and cytochrome c subunit ( cox 1) mtDNA sequences for three previously undescribed proterodiplostomids collected from Crocodylus spp. in Australia and South Africa. The newly generated 28S sequences were used to examine phylogenetic affinities of these taxa. All three newly sequenced proterodiplostomid species appeared in the phylogenetic tree in a strongly supported monophyletic clade comprising exclusively parasites of Crocodylus . http://www.zoobank.org/urn:lsid:zoobank.org:pub:C30F977D-4A0B-4D8C-8BAF-0D6C48B5396B